Azadirachta indica triterpenoids promote osteoblast differentiation and mineralization in vitro and in vivo - Kushwaha, Priyanka; Khedgikar, Vikram; Haldar, Saikat; Gautam, Jyoti; Mulani, Fayaj A.; Thulasiram, Hirekodathakallu V.; Trivedi, Ritu (Bioorganic & Medicinal Chemistry Letters, 2016)
Terpenoids were isolated using chromatographic purification through solvent purification technique and identified as Azadirone (1), Epoxyazadiradione (2) Azadiradione (3) Gedunin (4) Nimbin (5) Salannin (6) Azadirachtin A (7) and Azadirachtin B (8) from Azadirachta indica. Out of eight compounds, only three compounds had osteogenic activity and enhanced osteoblast proliferation, differentiation and mineralization in osteoblast cells. Active compounds stimulated osteogenic genes ALP, RunX-2 and OCN expressions in vitro, but Azadirachtin A had a maximum ability to stimulate osteoblast differentiation and mineralization compared to other two active compounds. For in vivo study, Azadirachtin A injected subcutaneously in pups, which enhanced osteogenic gene expressions and promoted bone formation rate significantly. Here, we conclude that active compounds of Azadirachta indica have osteogenic activity and Azadirachtin A has a beneficial effects on bone. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ALP and mineralization assay; Balb/c mice pups; Calvarial osteoblast cells; Gene expressions

Azadirachtin-A from azadirachta indica impacts multiple biological targets in cotton bollworm helicoverpa armigera - Dawkar, Vishal V.; Barage, Sagar H.; Barbole, Ranjit S.; Fatangare, Amol; Grimalt, Susana; Haldar, Saikat; Heckel, David G.; Gupta, Vidya S.; Thulasiram, Hirekodathakallu V.; Svatos, Ales.; Giri, Ashok P. (ACS Omega, 2019)
Azadirachtin-A (AzaA) from the Indian neem tree (Azadirachta indica) has insecticidal properties; however, its molecular mechanism remains elusive. The ``targeted and nontargeted proteomic profiling'', metabolomics, matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) imaging, gene expression, and in silico analysis provided clues about its action on Helicoverpa armigera. Fourth instar H. armigera larvae fed on AzaA-based diet (AzaD) suffered from significant mortality, growth retardation, reduced larval mass, complications in molting, and prolonged development. Furthermore, death of AzaD-fed larvae was observed with various phenotypes like bursting, blackening, and half-molting. Liquid chromatography-mass spectrometry (LC-MS) data showed limited catabolic processing of ingested AzaA and dramatic alternations of primary metabolism in H. armigera. MALDI-TOF imaging indicated the presence of AzaA in midgut of H. armigera. In the gut, out of 79 proteins identified, 34 were upregulated, which were related to digestion, immunity, energy production, and apoptosis mechanism. On the other hand, 45 proteins were downregulated, including those from carbohydrate metabolism, lipid metabolism, and energy transfer. In the hemolymph, 21 upregulated proteins were reported to be involved in immunity, RNA processing, and mRNA-directed protein synthesis, while 7 downregulated proteins were implicated in energy transfer, hydrolysis, lipid metabolism, defense mechanisms, and amino acid storage-related functions. Subsequently, six target proteins were identified using labeled AzaA that interacted with whole insect proteins. In silico analysis suggests that AzaA could be efficiently accommodated in the hydrophobic pocket of juvenile hormone esterase and showed strong interaction with active site residues, indicating plausible targets of AzaA in H. armigera. Quantitative polymerase chain reaction analysis suggested differential gene expression patterns and partly corroborated the proteomic results. Overall, data suggest that AzaA generally targets more than one protein in H. armigera and hence could be a potent biopesticide.

Accurate identification of bioactive meliaceae limonoids by UHPLC-MS/ms based structure-fragment relationships (SFRs) - Mulani, Fayaj A.; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, V, Hirekodathakallu (ACS Omega, 2021)
Y Limonoids are bioactive plant specialized metabolites found in the Meliaceae family. The basic limonoids, i.e., azadiradione, epoxyazadiradione, and gedunin have been exploited for various bioactivities and therefore are the potential drug leads for tomorrow. However, their low abundance, structural similarity, and lack of adequate mass fragmentation data have hampered their accurate identification and quantification from various sources. In the present study, basic limonoids such as azadirone, azadiradione, epoxyazadiradione, and gedunin isolated from Neem were utilized for the synthesis of their derivatives and isotopologs. A total of 30 one compounds were used in this study among which five were isolated, two were biotransformed, and 24 were synthesized. Among the synthesized compounds nine are novel compounds including six deuterated analogs/isotopologs which are (1,3-H-2)-1,2dihydro-3 beta-hydroxyazadiradione (9), (1,3,16-H-2)-1,2-dihydro-3 beta-16 beta-dihydroxyazadiradione (10), 3 beta-hydroxyazadiradione (11), 3 beta-16 beta-dihydroxyazadiradione (12), (3-H-2)-3 beta-hydroxyazadiradione (13), (3,16-H-2)-3 beta-16 beta-dihydroxyazadiradione (14), (1,3,7-H-2)-1,2-dihydro-3 beta-hydroxy-7-deacetylazadiradione (15), 1,2,20,21,22,23-hexahydroazadiradione (17), and (1,3-H-2)-1,2-dihydro-3 beta-hydroxygedunin (29). These limonoids along with their semisynthesized derivatives were subjected to ultra high performance liquid chromatography mass spectrometry (UHPLC-MS/MS) and the fragmentation pathway was established based on structure-fragment relationships (SFRs), utilizing high resolution MS/MS data. We have developed a most reliable and easily reproducible protocol describing in depth analysis of SFRs based on the structural modifications and synthesis of isotopologs. Also, the MS/MS fragment library of these basic limonoids generated in this study acts as a fingerprint for accurate identification and quantification of limonoids by MS/MS analysis in various plant tissue extracts, phytopharmaceutical formulations and biological samples.